Análisis socio-jurídico de casos de despido intempestivos a los trabajadores de la ciudad de Machala en el período 2007-2008. - Dumes Castillo, Mariuxi Alexandra (2008)
The worrying unemployment in our city, caused by job layoffs, different questions and concerns of people who have labor problems and do not know what to do when they are unexpectedly laid off, many times for illegal because generating sector job uncertainty and assumptions of violation of workers' rights.